Relativity Lite A Pictorial Translation of Einstein’s Theories of Motion and Gravity - Straton, Jack C. (Open textbook library., 2020)
Relativity Lite is designed for courses like my 100-student General Astronomy sequence. Relativity Lite translates the mathematical equations conventional relativity texts rely upon into pictures that are readily understood and contain within them the mathematical essentials. This new book would provide the comprehensive coverage needed to understand, in sufficient depth, these three linked areas of our reality.